Neuropsychological impairment associated with depression (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
The aim of the present paper is to describe the main cognitive impairment found in the depression, as well as its correlations with neuroimage studies. It is not clear, however, if the impairment would be related to disturbed cerebral functioning or to an epiphenomenon of disordered mood or depressive rumination. This review will emphasize the importance of neuropsychological assessment in the elderly in order to improve the differential diagnosis between dementia and pseudodementia, as well as to describe factors that can predict cognitive impairment in depression, as for example, psychotic features.